2022
DOI: 10.17219/dmp/145065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Simonart’s band in cleft children at a cleft center in Indonesia: A nine-year retrospective study

Abstract: Background. Simonart's band is a soft tissue band that connects the cleft gap of the base of the nostril or the margin of the alveolus. While research on the prevalence of Simonart's band in cleft lip and palate cases has been carried out in various countries, research on Simonart's band in Indonesia has yet to be conducted.Objectives. This study aimed to determine the prevalence of different types of Simonart's band at a cleft center in Indonesia.Material and methods. The data of cleft patients were reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…From the qualitative aspect, it was observed that width of cleft and Simonart’s band play an essential role in the outcome with wider clefts compromising the Steffensen parameters[ 5 6 ] [ Table 2 ]. The presence of Simonart’s bands indicates abnormal positioning of the tissues and the connective tissue activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the qualitative aspect, it was observed that width of cleft and Simonart’s band play an essential role in the outcome with wider clefts compromising the Steffensen parameters[ 5 6 ] [ Table 2 ]. The presence of Simonart’s bands indicates abnormal positioning of the tissues and the connective tissue activity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the basic demographic details of gender, age (in months at time of surgery, nearest to 2 decimals), cleft width (if gap is ≤ 10 mm, it is narrow, >11 mm would be a wide cleft), presence of lip-lip Simonart’s band (present/absent)[ 5 6 ] were noted down. From the ≥ 1 year post-operative follow-up images, four anthropometric parameters were measured using the post-operative photographs: lip height, lip width, vermilion height and alar base width [ Figure 3 ].…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, achieving esthetic and functional restoration in cleft patients can be challenging due to various types of malocclusion and a tendency for relapse after orthodontic treatment. The presence of soft tissues, such as Simonart's band, also adds complexity to the treatment process [7,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons may be dental anomalies, which have been shown to be higher in individuals with cleft compared to the normal population [ 19 ], including dental agenesis, supernumerary teeth, microdontic upper lateral incisors, the ectopic eruption of teeth, delayed tooth eruption, and enamel hypoplasia, which are frequent in these patients [ 13 , 14 , 20 , 21 ]. Additionally, the presence of soft tissue bands connecting the cleft to the base of the nostril or the alveolar margin, known as Simonart’s bands, is common [ 22 , 23 ]. These bands may contribute to a higher prevalence of distal upper lateral incisors to the cleft compared to patients without this condition [ 23 ].…”
Section: Introductionmentioning
confidence: 99%